Implementation of the Project Based Learning (PjBL) Learning Model to Improve Student Learning Outcomes on Design Material at Canva in Informatics Subjects - Deni Sartika; Yuliawati Yunus (SAFE-Network, 2025)
This study aims to improve student learning outcomes using the Project Based Learning learning model on Design Material in Canva in Informatics Subjects at SMA Negeri 6 Padang class XII MIPA academic year 2024-2025. This study uses a classroom action research method which is a type of qualitative research that emphasizes the process, designed to achieve improvements in practice and real situations in the classroom. The research subjects were class XII MIPA 1 as many as 36 students. The results of the study can be concluded that student activity in each cycle is increasing. This can be seen from the student learning outcomes that have improved. The average initial value is 61.75 with a percentage of completeness of 33.33% (category is not good) so that cycle I is carried out. In cycle I, student learning outcomes with an average value of 79.58 with a percentage of completeness of 72.22% (Enough) increased from the initial value, but there are still shortcomings so that improvements are needed in cycle II. In cycle II, there was an increase in student learning outcomes with an average score of 84.44 and a completion percentage of 91.67% (very good). The implementation of the Project-Based Learning (PjBL) model is very effective in improving and encouraging student learning outcomes to a better level. With this model, Informatics learning becomes more interesting, interactive, and meaningful, thus helping students achieve optimal results.